The Theatre of the Occult Revival - Lingan, E. author. aut Link
XIV, 247 p. 13 illus.
Keywords: This book explores the religious foundations, political and social significance, and aesthetic aspects of the theatre created by the leaders of the Occult Revival. Lingan shows how theatre contributed to the fragmentation of Western religious culture and how contemporary theatre plays a part in the development of alternative, occult religions.